2022
DOI: 10.3390/en15030942
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of Electric Vehicles in Hong Kong

Abstract: Road vehicles are responsible for air pollution in Hong Kong, and electric vehicles (EVs) are a promising alternative to internal combustion engine vehicles as the city is transitioning to clean energy. In this work, EV adoption in Hong Kong is investigated and analyzed, including the global EV markets, present EV status in Hong Kong, local challenges facing EV development, suggestions for EV promotion in Hong Kong, emerging technologies, and decommissioning of batteries and EVs. The challenges of EVs include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…In the Smart City Blueprint Consultancy Study Report published in June 2017, the Hong Kong Government proposed the following strategic measures for smart mobility involving CVs [112]:…”
Section: Hong Kongmentioning
confidence: 99%
“…In the Smart City Blueprint Consultancy Study Report published in June 2017, the Hong Kong Government proposed the following strategic measures for smart mobility involving CVs [112]:…”
Section: Hong Kongmentioning
confidence: 99%
“…In particular, the survey discusses grid codes, connection agreements, tariffs, and market platforms as a means to promote a more extensive role for EVs in providing flexibility services. Mo et al [13] explored strategies to increase EV penetration in order to address air pollution issues in Hong Kong and other major cities. The authors identified obstacles for the proliferation of EVs (e.g., insufficient charging infrastructures and inadequate management of public charging facilities) as well as measures to promote EVs (e.g., incentives and bonuses for EVs and offering high-power quick-charging facilities).…”
Section: State Of the Art Of The Researchmentioning
confidence: 99%
“…With the increasing popularity of electric vehicles [7], the demand for LIBs with high-energy densities is growing, driven by concerns over driving range [8][9][10][11]. Silicon-based anodes offer significantly larger mass/volume capacities compared to traditional materials.…”
Section: Introductionmentioning
confidence: 99%